Hot water treatment in autonomous heat supply systems with several water intake points - A. L. Toropov (Vestnik MGSU)
Introduction. Improving the energy efficiency of HVAC equipment makes the greatest contribution to reducing the man-made impact on the environment. The peculiarities of using gas heaters for several hot water disassembly points are related to the comfort of hot water consumption. Two points are included in this concept. The delay in the start time of hot water supply from the moment the tap is opened and the fluctuation of hot water temperature when several water intake points are used at random at the same time. The aim of the study is to investigate the operating modes of hot water of gas heaters, to determine the influence of algorithms for modulation of thermal power and thermal inertia of heat exchangers on the change in the temperature of hot water supply with the simultaneous use of two water intake points.Materials and methods. The study was carried out on the research stand of the “ARDERIA” plant. Objects of research — Gas Instantaneous Water Heater with Thermal Power Modulation Ariston FAST EVO ONT C 14, Arderia D24 and Arderia D24 Atmo wall-mounted gas boilers.Results. The coefficients of thermal inertia of the heat exchangers of the studied specimens, the value of temperature change at the main point of water intake (shower) during periodic connection and disconnection of the tap in the kitchen were determined. Comparisons of the thermal power modulation algorithms of the specimens under consideration are given.Conclusions. Operation of autonomous hot water supply systems with several water intake points leads to water temperature fluctuations with a range of up to 10 °C. Water temperature equalization time is up to one and a half minutes. The solution to the issue of ensuring a given comfortable level of water temperature is achieved by organizing the consumption of hot water and cold water in accordance with the level of priority of water consumption at various water intake points, the use of buffer heat tanks or heat generators with a large range of heat power regulation and reduced thermal inertia of heat exchangers.